Dinamika Kurikulum Madrasah Berbasis Pesantren Pada Abad Ke-20 (Analisis Historis Implementasi Kurikulum Madrasah) - Maghfuri, Amin; Rasmuin, Rasmuin (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Madrasa is an Islamic educational institutions that play a role in realizing national education goals. But in its history, the existence of madrassas has experienced complex dynamics and tides. This study was intended to analyze the dynamics and the development of the implementation of the madrasa curriculum, especially those based on Islamic boarding schools in the 20th century. The approach used in this study is a qualitative approach using the documentation method. The results showed that the curriculum dynamics of pesantren-based madrasas in their history experienced various dynamics that could be classified into three groups, namely periods of growth, periods of development, periods of strengthening of existence. The growth period starts from the birth of madrassas from the pesantren's womb and curricula that are dominated by religious knowledge and tend not to be neatly structured. The development periods are characterized by many of fluctuations and tugging on the implementation of the madrasah curriculum mainly because it is related to recognition and existence. The period of strengthening existence began when the existence of madrassas was legally recognized, especially after the issuance of three Ministerial Decrees which emphasized improving the quality of madrasah education.